"Beyond an acronym, STEM is…": Perceptions of STEM. (24th December 2020) - Navy, Shannon L.; Kaya, Fatma; Boone, Brian; Brewster, Christine; Calvelage, Kelly; Ferdous, Tanzimul; Hood, Ebony; Sass, Laura; Zimmerman, Maggie
Abstract: Although STEM is at the forefront of many educational initiatives, little is known about various professionals' perceptions of STEM. This mixed‐methods study surveyed 164 preservice teachers, inservice teachers, administrators, informal educators, and STEM professionals. Quantitative and qualitative questions on the survey elicited participants' perceptions of STEM, STEM support, and STEM careers. Quantitative analysis revealed that profession influenced understandings of STEM, importance of STEM, support for STEM, and perceptions of STEM career opportunities. Qualitative analysis provided rich explanations for the differences in perceptions among professions. This study suggests that science teacher educators need to ensure preservice teachers have understandings of STEM and STEM careers, K‐16 educators need to emphasize the current importance of STEM, and administrators and policymakers need to align visions of STEM with curriculum and pacing guides so teachers feel supported in their STEM endeavors.